Analisis Kemampuan Literasi Sains Siswa dalam Upaya Mewujudkan Karakter Peduli Lingkungan di Sekolah Adiwiyata SDN Karang Mulya - Lustianti, Devina; Syamsi, Atikah; Atikoh, Nur (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research is motivated by a phenomenon that occurs, namely the environmentally conscious character of students who are already good because they attend Adiwiyata schools. Teachers at SDN Karang Mulya implement various efforts to realize and develop the environmentally caring character of their students, one of which is through learning based on scientific literacy. Seeing the phenomenon that occurred at the school in question, the researchers were interested in taking a more in-depth picture of the students' already good environmentally caring character by looking at the students' scientific literacy abilities. This research aims to (1) determine the scientific literacy abilities of class V students at SDN Karang Mulya. (2) know the ways or efforts to realize the character of caring for the environment. (3) find out the implications regarding scientific literacy skills in realizing environmentally caring character. This research uses a qualitative approach with descriptive methods. The data collection techniques used were interviews, observation and documentation. The subjects of this research were teachers and students of class V at SDN Karang Mulya. This research data was analyzed by data reduction, data presentation, and drawing conclusions or verification. The results of this research are that the average scientific literacy ability of students at SDN Karang Mulya is 80%. Meanwhile, the average environmentally conscious character of class V students at SDN Karang Mulya is 76.25%. The implications for teachers are, if students have good scientific literacy skills, it will be easier for teachers to carry out the learning process in class and teachers will also find it easier to realize and develop students' environmentally caring character. Meanwhile, the implication for schools is that if students have a good environmentally caring character, such as throwing rubbish in the right place according to its type, always carrying out daily pickets, carrying out reforestation, utilizing used plastic goods, and doing community service, the school environment will always be clean, comfortable and beautiful.